Asiorrhina, a new Oriental genus of Lygistorrhinidae (Diptera: Sciaroidea) and its phylogenetic position - Blagoderov, Vladimir; Hippa, Heikki; Ševčík, Jan (Zootaxa, 2009)
A new genus of Lygistorrhinidae, Asiorrhina gen. n., and a new species, Asiorrhina parasiatica sp. n., are described. Asiorrhina asiatica (Senior-White) comb. n. is redescribed and selected as the type species for the new genus. The systematic position of the new genus is discussed. All recent taxa of Lygistorrhinidae form a monophyletic group with the fossil genus Palaeognoriste Meunier as the sister group.